Microbial Laccase and its Applications in Bioremediation - Roohi; Jain, Neha; W. Ramteke, Pramod (Current Biochemical Engineering (Discontinued), 2016)
Our biosphere is under constant threat from continuing environmental pollution. Different approaches have been practiced to decipher anthropogenic environmental hazards. Green chemistry and use of enzymes like laccases are some of the most highlighted practices in reducing the adverse effects on our surroundings. Laccases are widespread enzymes belong to oxidase group present mainly in fungi, some higher plants and a few bacteria. These enzymes are studied well in detail in the last decades since they can catalyze the oxidation of variety of diamines, aromatic amines, phenolic compounds, lignin related compounds as well as environmental pollutants that are highly recalcitrant with simultaneous reduction of molecular oxygen to water. Laccases have great biotechnological and industrial potential because of their diverse functions: pigment formation, lignin degradation and detoxification of colored industrial effluents including xenobiotics mostly from the textile, petrochemical industries, paper and pulp. Laccases are multifunctional enzymes which can be used for the manufacture of anti-cancer drugs, in certain water purification systems as cleaning agents, as bioremediation agent and even as ingredient of several cosmetics. Laccases can be further used in beverage processing, as biosensor to improve food sensory parameter, for ascorbic acid determination and for sugar gelation of beet pectin. This review focuses on the structure, properties and scope of laccases mainly in bioremediation and also in other industrial fields.
Keywords: bioremediation